The Number of Alveolar Bone Cells Exposed to Zoledronate in the Post-Tooth Extraction Socket - Lubis, Septina Sabilla; Palupi, Anggraeny Putri Sekar; Komariah, Komariah; Latief, Benny Syariefsjah; Priosoeryanto, Bambang Pontjo; Suniarti, Dewi Fatma (Journal of Syiah Kuala Dentistry Society, 2024)
Background: Zoledronate is an intravenous bisphosphonate that effectively treats osteoporosis by inhibiting osteoclast resorption, thereby reducing the risk of fractures. However, its use in post-extraction patients may increase the risk of bisphosphonate-related osteonecrosis of the jaws (BRONJ). Objective: This study aims to analyze the effects of zoledronate on alveolar bone structure in Sprague Dawley rats, focusing on changes in osteoblast, osteocyte, and osteoclast counts. Methods: This cross-sectional study employed an observational analytical approach. Samples were categorized based on zoledronate exposure. Osteoblast, osteocyte, and osteoclast counts were measured using ImageJ software at 40x magnification. Data were analyzed using SPSS, with one-way ANOVA employed for statistical analysis. Normality and homogeneity tests were conducted to ensure data validity. Results: Zoledronate exposure resulted in a decrease in osteoblast and osteoclast counts, while osteocyte counts increased. Statistical analysis showed no significant differences between the zoledronate-exposed group and the control group. Conclusion: Zoledronate reduces osteoclasts and increases osteocytes, potentially leading to cellular apoptosis in osteoporosis patients. The risk of BRONJ can be minimized by administering zoledronate at appropriate doses and maintaining optimal oral hygiene to prevent bacterial activity.